Contribution to the development of pharmaceutical education in Costa Rica: Professional academic profile of Costa Rican assistencial pharmacist - Badilla Baltodano, Beatriz (2018)
We present a research of  qualitative type that contributes to the development of pharmaceutical education in Costa Rica, through a proposal of professional academic profile (PAP) of the person who practices in the area of pharmacy assistance, area of greater professional performance in our The PAP presented three integral areas: cognitive, attitudinal and work. The knowledge of the cognitive area was classified according to the categories established by the Ibero-American Conference of Faculties of Pharmacy and the Professional Professionals were listed according to the functions, activities and tasks established for pharmacists by the International Pharmaceutical Federation and the World Health Organization. The PAP proposed to encompass the necessary link between the curricular design of the curriculum and the expected professional exercise. It is conceived as the characteristic of the type of professional in the pharmacy sought by higher education institutions, considering the academic interests of the universities, also the labor commitment in the social sector and the reason that makes it valuable. universities that offer the career of Pharmacy and for SINAES they compose it in their quality criteria. The work team and the advice of the National System of Accreditation of Higher Education (SINAES) collect, review and guide the national and international references in the training of pharmaceutical professionals, study plans and other bibliographic sources, as well as interviews with leading professionals. Methodologically, the profile proposal was a three validation processes that resulted in the final document